Utilization of sugarcane bagasse cellulose for producing cellulose acetates: novel use of residual hemicellulose as plasticizer - Shaikh, Hamid M.; Pandare, Kiran V.; Nair, Greeshma; Varma, Anjanikumar (Carbohydrate Polymers, 2009)
Sugarcane bagasse was fractionated to cellulose, hemicellulose and lignin by a proprietary steam explosion process, followed by downstream purifications, developed in our laboratory. The fractionated cellulose contained similar to 94% cellulose, about similar to 5% hemicellulose, traces of lignin (similar to 0.2%), and similar to 1% ash. The cellulose was acetylated under heterogeneous conditions to obtain cellulose acetates. These were extensively characterized using FTIR, TGA, DSC, GPC, HPIC, WAXRD, and viscometry. The novel feature of this study was the utilization of the hemicellulose content (5%) of bagasse cellulose as an internal plasticizer. Through kinetic experimentation, we have demonstrated that the residual hemicellulose need not be considered as an impurity; rather it can be used in acetylated form as a plasticizer as well as a biodegradable additive for cellulose acetates made from slightly impure cellulose produced from non-wood origin. Our results therefore show how lignocellulosic agricultural wastes can be utilized to produce high value plastics. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bagasse cellulose; Cellulose acetate; Hemicellulose; Plasticizer; Sugarcane bagasse; Xylan acetate

Catalytic upgrading of citric acid to environmental friendly tri-butyl citrate plasticizer over ultra stable phosphonated Y zeolite - Nandiwale, Kakasaheb Y.; Gogoi, Pranjal; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
The catalytic synthesis of non-toxic/eco-friendly tributyl citrate (TBC) plasticizer by esterification of renewable citric acid (CA) with butanol would be completely sustainable route. In this context, catalytic performance of parent ultra stable Y (USY) and phosphonated USY catalysts were investigated for TBC synthesis. Parent USY and phosphonated USY catalysts were characterized by powder X-ray diffraction (XRD), N-2 adsorption-desorption, NH3 temperature programmed desorption (TPD), pyridine-Fourier Transform Infrared Spectroscopy (FTIR), FTIR, SEM, ICP. The influence of various process parameters such as phosphorous (P) loading (0 to 4 wt/%), catalyst loading (5-25%), molar ratio of CA to n-butanol (1:4 to 1:12), reaction temperature (383-423 K) and reaction time (1-5 h) have been investigated over USY catalyst with aim to maximize CA conversion and TBC yield. Amongst the studied catalysts, the 2% (w/w) P/USY was found to be highly potential catalyst with complete CA conversion (100%) and 93% TBC yield. The present method of using 2% (w/w) P/USY catalyst for the synthesis of TBC would be environmentally benign in the context of bio-renewable synthetic route, high catalytic activity, non-toxic product, long term stability and reusability of catalyst (five catalytic cycles). (c) 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved,
Keywords: Butanol; Citric acid; heterogeneous catalysis; Plasticizer; Tributyl citrate